Isotopic composition of leaf carbon (δ13C) and nitrogen (δ15N) of deciduous and evergreen understorey trees in two tropical Brazilian Atlantic forests. (17th April 2018) - Vitória, Angela Pierre; Ávila-Lovera, Eleinis; de Oliveira Vieira, Tatiane; do Couto-Santos, Ana Paula Lima; Pereira, Tiago José; Funch, Ligia Silveira; Freitas, Leandro; de Miranda, Lia d'Afonseca Pedreira; Rodrigues, Pablo J. F. Pena; Rezende, Carlos Eduardo; Santiago, Louis S.
Abstract: Isotopic composition of leaf carbon (δ 13 C) and nitrogen (δ 15 N) is determined by biotic and abiotic factors. In order to determine the influence of leaf habit and site on leaf δ 13 C and δ 15 N in the understorey of two Atlantic forests in Brazil that differ in annual precipitation (1200 and 1900 mm), we measured these isotopes in the shaded understorey of 38 tropical tree species (20 in the 1200-mm site and 18 in the 1900-mm site). Mean site values for δ 15 N were significantly lower at the 1200-mm site (−1.4‰) compared with the 1900-mm site (+3.0‰), and δ 13 C was significantly greater in the 1200-mm site (−30.4‰) than in the 1900-mm site (−31.6‰). Leaf C concentration was greater and leaf N concentration was lower at 1200-mm than at 1900-mm. Leaf δ 15 N was negatively correlated with δ 13 C across the two sites. Leaf δ 13 C and δ 15 N of evergreen and deciduous species were not significantly different within a site. No significant phylogenetic signal for any traits among the study species was found. Overall, site differences were the main factor distinguishing traits among species, suggesting strong functional convergence to local climate and soils within each site for individuals in the shaded understorey.